Formas de tratamento no português brasileiro do século XX: conservação e variação em cartas pessoais do Norte e Nordeste - Araújo, Francisco Jardes Nobre de (2019)
Unlike most Indo-European languages, Portuguese presents a vast repertoire of ways to treat the interlocutor, from the most intimate to the most reverential. The present study investigates the use of forms of treatment in a community of practice, the Assembly of God, based on 139 letters written from 1940 to 1986 to the pastor José Alencar de Macedo, who spread the church through the interior of the state of Ceará and border region with Rio Grande do Norte and Paraíba, in northeastern Brazil. Based on the assumption that the forms of treatment codify relations between the interlocutors, but are also subject to variations motivated by structural factors of the linguistic system, a two-step analysis was carried out: the first, according to Historical Sociolinguistics, is based in Brown and Gilman (1960) and aims to apply the T/V Distinction (also known as Theory of Power and Solidarity) to the sample, identifying the forms T (of solidarity / intimacy) and the forms V (of power / formality) used in the treatment of the recipient pastor; the second, according to Variationist Sociolinguistics, is based on Weinreich, Labov and Herzog (1968) and aims to investigate the relevant linguistic constraints in the choice of clitics and possessives with reference to the interlocutor. The first analysis found a system of treatment in relative balance in the letters of the family members of the pastor, but in conflict in the extrafamilial letters. In symmetrical family relationships, the treatment is done with T forms, since the canonical P2 predominates almost categorically (letters of sisters), or the canonical P2 in variation with você and P3 forms (letters of brothers-in-law); in the asymmetrical family relations, the treatment is made with V forms, being o senhor with P3 pronouns the dominant forms; in the extra-familial relations, both symmetrical and asymmetrical, there is a vast repertoire that goes from the intima of tu to vós of formality, but o irmão is the most recurrent form of treatment. The second analysis, which used the GoldVarb X program, revealed that the alternating use of clitics and possessives is mainly guided by the principle of formal parallelism, predominating lhe (134/273 or 49.1%) between the clitics and seu (226/389 or 58%) among the possessives, which indicates that, in such sample of letters, these forms outperformed the canonical P2 competitors (te and teu, respectively).